Peramalan Inflasi di Wilayah Purwokerto dengan Metodologi Box-Jenkins - Endang Setiasih; Rakhmat Priyono (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2009)
Basically, inflation constitutes a problem than solution because its impact to all economic conditions. Inflation phenomena in Purwokerto is necessary to research. Inflation in this region is more unstable than other cities. December 2008, even other cities had deflation situation, positive inflation occurred in Purwokerto.Estimated inflation shows that Purwokerto inflation have no trend condition. By assumption no cycles factor, statistically inflation have seasonal and irregular term pattern. From average seasonal factor, it is identified that higher inflation than other months will occur to January, February, March, June, and July. While in irregular term factor, it is identified extreme inflation was occur on March 2005, September 2005, October 2005, December 2005, and July 2008. Increasing of petroleum price was related to those extreme inflation.Inflation forecasting analysis shows better differentiation for estimated inflation is on 1st degree. From alternatives modeling, estimated inflation model is statistically better if it includes autoregressive factors for 1st and 2nd month before and moving average from 1st to 5th month before. Keyworlds: inflation, box-jenkins methodology, serial decomposition